KECURANGAN LAPORAN KEUANGAN DILIHAT DARI ASPEK KONDISI KEUANGAN DAN PENGAWASAN DEWAN KOMISARIS INDEPENDEN - Neta Belinda; Zaky Machmuddah (Universitas Budi Luhur, 2024)
Detecting whether financial target variables, ineffective monitoring, financial distress are able to influence fraud in financial reports is the aim of this research. Measuring financial statement fraud uses the F-Score. The measurement of the financial target variable uses ROA, while the measurement of the ineffective monitoring variable uses BDOUT, and the measurement of the financial distress variable uses G-Score. This type of research is quantitative using data sourced from the company website. The research population includes the properties & real estate sector listed on the IDX with observation periods from 2018 to 2022. The data obtained was 156 observation data after going through the purposive sampling stage. After going through various stages of research, the conclusion was found that financial statement fraud can be influenced by financial targets that are under pressure, but cannot be influenced by ineffective monitoring because good monitoring is measured through quality not quantity or financial distress because perhaps the company’s focus on improving its operations is not on how to report fraud his finances.